PENGARUH COUNTERING AMERICA’S ADVERSARIES THROUGH SANCTIONS ACT (CAATSA) TERHADAP MODERNISASI ALUTSISTA UDARA INDONESIA - Muhammad Farrel Anggaraksa; Mhd Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT This research analyzesthe effect of Countering America's Adversaries Through Sanctions Act (CAATSA) on the modernization of Indonesia's defense equipment. CAATSA has made a lot of losses in several countries, one of which is a loss in the economy. In mid-2017 to be precise in July-August, the United States government ratified this law. This was due to Russia's interference in Ukraine and Syria. Indonesia is committed to developing the defense industry, especially air defense, as stated in Law No. 16 of 2012 concerning the Defense Industry. Therefore Indonesia bought 11 SU-35 aircraft from Russia with a counter-trade system to strengthen its defense. However, due to the ratification of the CAATSA law, several countries have been subject to sanctions, such as Turkey, China and India. Because of this, Indonesia must rethink in modernizing its air defense. In this research,the authors used qualitative data analysis techniques, this is because the empirical data obtained by the authors is qualitative data in the form of a collection of words and not a series of numbers. with data collection techniques through literature study sourced from several books, journals, articles, websites and also requests for research data from relevant agencies. This study uses the perspective of Realism and Coercive Diplomacy Theory. The result of this paper is that Indonesia as a country has a policy of not buying the United States' air defense equipment based on CAATSA pressure. However, the impact of this policy was that Indonesia canceled the purchase of Russian SU-35 aircraft on the grounds of avoiding sanctions and Indonesia switched to buying 36 French Dassault Rafale aircraft to strengthen the country's main combat defense system. where this became a maneuver of Indonesia's foreign policy in modernizing its defense equipment. Keywords: Countering America's Adversaries Through Sanctions Act, CAATSA, modernization of Indonesia's,